The Effect of Describing Picture Strategy in Teaching Writing of The Descriptive Text at Tenth Grade in MA Hidayatut Tauhid Labuhan Haji 2022/2023 - Zohir, Muhammad; Putera, Lalu Jaswadi; Baharudin, Baharudin; Sahudin, Sahudin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The aims of this research are to improve the students writing ability of tenth grade of MA Hidayatut Tauhid by applying describing picture strategy. The research method used is pre-experiment with one group pretest and posttest design, The population of this study is grade 10 MA Hidayatut Tauhid, and the research sample is 22 grade 10 students of MA Hidayatut Tauhid, The sampling technique used is total sampling. The data inference methods used are pretest and posttest, before being given a posttest, students are given treatment for 3 times using the describing picture strategy in learning to write descriptive text. The results of this study showed that the posttest score was greater than the pretest value (85.55>68.23) and the t-test value was greater than the t-table value (1.721). In addition, the Sig.1- and 2-sided value of 0.01 was smaller than 0.05 (0.01<0.05) This shows that there is a difference in the mean score between the pretest and the posttest. So, it can be concluded that Ha is accepted and H0 is rejected, in other words describing picture strategy has a significant effect toward student's writing descriptive text at MA Hidayatut Tauhid Labuhan Haji.